Reason and Assessment of Postural Control Deficits of Chronic Obstructive Pulmonary Disease - Xueqing SHI; Ying OUYANG; Yinlin SHAO; Yi WU (康复学报)
Chronic obstructive pulmonary disease (COPD) is a kind of common systematic disease, characterized by continuous airflow obstruction. The high morbidity and disability caused by COPD bring the patients, their families and community huge psychological and economic pressures. The pulmonary rehabilitation (PR) weighs extremely high in the guidelines among the world and is widely accepted by patients, physicians and physiotherapists. Traditionally, the PR program focused on the respiratory related impairments, mainly consisted of pulmonary hygiene, respiratory muscle reduction and aerobic training, but the assessment and intervention of postural control were often neglected, which caused various functional limitations. Postural control means the ability to control the center of gravity into the limit of stability of the base of support. The deficit of postural control was characterized by highly risk of fall, which would cause high prevalence of morbidity and mortality. This kind of deficit was widely reported in several articles and case reports, but there was no common sense on the mechanism behind of it. Thus this article summarized the mechanism and the assessment of the deficit of postural control among COPD patients recent years.